SEASONALITY AND RURALITY – SECOND HOMES AND TOURISM IN RURAL AREAS OF SERBIA - Terzić, Aleksandra; Jovičić Vuković , Ana; Petrevska, Biljana (Economics of Agriculture, 2024)
The study investigates the growing phenomenon of second homes in rural Serbia and its implications for tourism development. By analyzing the geographical distribution of second homes and their relationship to the territorial capital, the study contributes to the understanding of rural tourism dynamics. The research identifies regions with high concentrations of second homes, often overlapping with attractive natural areas and renowned tourist centers. This overlap with peak tourist seasons intensifies environmental and social pressures on already fragile rural areas. To mitigate these pressures and promote sustainable tourism development, the study advocates for region-specific policies, improved infrastructure and the implementation of sustainable tourism practices. By leveraging second homes as potential rural tourism accommodations, policymakers can support local communities, lesser the environmental disturbance and promote responsible tourism.